Molecular mechanisms of semaglutide and liraglutide as a therapeutic option for obesity - Tamayo-Trujillo, Rafael; Ruiz-Pozo, Viviana A.; Cadena-Ullauri, Santiago; Guevara-Ramírez, Patricia; Paz-Cruz, Elius; Zambrano-Villacres, Raynier; Simancas-Racines, Daniel; Zambrano, Ana Karina (Frontiers in Nutrition, 2024)
Obesity, a chronic global health problem, is associated with an increase in various comorbidities, such as cardiovascular disease, type 2 diabetes mellitus, hypertension, and certain types of cancer.The increasing global prevalence of obesity requires research into new therapeutic strategies.Glucagon-like peptide-1 receptor agonists, specifically semaglutide and liraglutide, designed for type 2 diabetes mellitus treatment, have been explored as drugs for the treatment of obesity. This minireview describes the molecular mechanisms of semaglutide and liraglutide in different metabolic pathways, and its mechanism of action in processes such as appetite regulation, insulin secretion, glucose homeostasis, energy expenditure, and lipid metabolism. Finally, several clinical trial outcomes are described to show the safety and efficacy of these drugs in obesity management.